Sri Lankan Public Health Midwives’ Knowledge on Maternal Mental Health Disorders - Kumarasinghe, Malith; Kasturiaratchi, Kaushalya; Irfaan, Shakira; Samarasinghe, Wasana; Hewamalage, Asiri (South Asian Journal of Social Sciences and Humanities, 2022)
Emotional support and services provided by Public Health Midwives (PHMs) play a crucial role in identification and management of maternal mental health disorders as they are the first line contact in maternal and child-care and the focal field health members in caring for the antepartum and postpartum mothers. Aim of this study was to describe the Sri Lankan PHMs’ knowledge on maternal mental health disorders. Cross-sectional descriptive study was conducted using probability proportionate sampling, covering PHMs of all districts in Sri Lanka. Total of 434 PHMs were recruited with 99.1% response rate. A content-validated pre-tested questionnaire was administered. Univariate and multivariate analysis was used to assess the knowledge of each component with selected study variables. Respondents’ mean age was 40.6 years. Out of the 430 PHMs, 36% of them were unaware, that symptoms of Depression and anxiety could be commonly seen during antenatal and postpartum period. It was found that only 21.8% of the respondents knew the average number of maternal deaths due to suicides in Sri Lanka. Forty seven percentage of the respondents did not know, that providing understanding, empathy and support was the most appropriate step in managing mothers with Postpartum Blues. This study findings highlight major deficiencies in basic knowledge of PHMs in identifying and initial management of common maternal mental health disorders. Therefore, focus on continuous professional development of PHMs should be prioritized.